The Spanish civil war - Parrilla (Aberdeen City Council, 1996)
Painting of Spanish republican soldiers marching with raised fists and waving republican and international brigade flags Poster advertising exhibition on the Spanish civil war, held in Aberdeen, 7 September-2 November, 1996. Original artwork from 1937 by Parrilla PO-0782